2021
DOI: 10.1108/idd-08-2020-0102
|View full text |Cite
|
Sign up to set email alerts
|

Twitter users’ coping behaviors during the COVID-19 lockdown: an analysis of tweets using mixed methods

Abstract: Purpose Using data from Twitter, the purpose of this paper is to assess the coping behaviour and reactions of social media users in response to the initial days of the COVID-19-related lockdown in different parts of the world. Design/methodology/approach This study follows the quasi-inductive approach which allows the development of pre-categories from other theories before the sampling and coding processes begin, for use in those processes. Data was extracted using relevant keywords from Twitter, and a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…While the communities in Myanmar tried to cope with the crisis in their own way, the health staff, mainly the staff who followed the Civil Disobedience Movement, showed their resilience by providing online consultation and counselling services, especially during the third wave of COVID-19. In the months to come, we could cultivate health system resilience by incorporating innovative models of digital health care as an alternative pathway [ 17. – 20.…”
Section: Discussionmentioning
confidence: 99%
“…While the communities in Myanmar tried to cope with the crisis in their own way, the health staff, mainly the staff who followed the Civil Disobedience Movement, showed their resilience by providing online consultation and counselling services, especially during the third wave of COVID-19. In the months to come, we could cultivate health system resilience by incorporating innovative models of digital health care as an alternative pathway [ 17. – 20.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have examined Twitter content to analyze how the public expresses their feelings at the onset of pandemics ( Baboukardos et al, 2021 ; Garcia & Berton, 2021 a; S. Kaur et al, 2020 ; Ridhwan & Hargreaves, 2021). By following a quasi-inductive approach, Mittal et al, (2021) found that the majority of Twitter users tend to share positive content regarding the lockdown but their opinions could swing over the course of pandemic based on recent developments. Some studies analyzed tweets with a focus on the public's emotions during the Covid-19 pandemic ( Gupta et al, 2021 ; Kabir & Madria, 2021 a), while others focused on public opinions following the rollout of Covid-19 vaccines ( Sv et al, 2021 ; Yousefinaghani et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature also suggests geographically different associations between local lockdown policies and public mental health. For example, Mittal et al [58] found that most Twitter users shared positive opinions toward lockdown policies in related tweets from March 22 to April 6, 2020, whereas another study focusing on Twitter users in Massachusetts found increased anxiety expression after the enforcement of the Massachusetts State of Emergency and US State of Emergency [59]. Notably, Wang et al [60] found that public sentiment toward lockdown policies was positive in most states (such as Michigan, North Carolina, and Pennsylvania) and negative in only a few states, including Ohio, which also demonstrates geographic variations of public reactions to lockdown policies.…”
Section: Comparison To Prior Workmentioning
confidence: 99%